Systems biology in drug discovery and development - Young, Daniel L.; Michelson, Seth (Hoboken, N.J. : Wiley, 2011)
This is the first comprehensive systems biology book to focus on its applications in drug discovery and development. Using real-world examples, the book shows how systems biology can be used to enhance pharmaceutical research and drug development. It highlights essential components of drug discovery like target identification and validation and complementary systems approaches like text-mining, large multi-context datasets and regression modeling. It also provides models for treatment personalization and methods for applying systems biology to pharmacokinetics, pharmacodynamics, and candidate biomarker indentification. Introducing key methods and technical approaches the book addresses the challenges currently facing the drug industry.
Introduction to systems biology in drug discovery and development -- Methods for in silico biology : model construction and analysis -- Methods in in silico biology : modeling feedback dynamics in pathways -- Simulation of population variability in pharmacokinetics -- Applications of systems biology approaches to target identification and validation in drug discovery -- Lead identification and optimization -- The role of core biological motifs in dose-response modeling : an example with switch-like circuits -- Mechanism based pharmacokinetic-pharmacodynamic modeling during discovery and early development -- Developing oncology drugs using virtual patients of vascular tumor diseases -- Systems modeling applied to candidate biomarker identification -- Simulating clinical trials -- Pathway analysis in drug discovery -- Functional mapping for predicting drug response and enabling personalized medicine -- Future outlook of systems biology.
Includes bibliographical references.
Print version record.
Keywords: Drug development; Systems biology; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; Drug development; Systems biology; Drug Discovery -- methods; Models, Biological; Pharmacokinetics; Pharmacological Phenomena; Systems Biology -- methods; Electronic books; Electronic books